Outcomes reported in randomized controlled trials of traditional Chinese medicine for acute pharyngitis: a scoping review - Danni Li; Chenyao Zhang; Yanjun Jin; Xinyao Jin; Fengwen Yang; Wentai Pang; Junhua Zhang (Frontiers in Pharmacology, 2026)
Purpose Considerable variability exists in the outcomes reported in trials of traditional Chinese medicine (TCM) for acute pharyngitis, limiting the comparability and applicability of findings. This review aimed to systematically examine outcome selection, measurement, and reporting in these studies to inform the development of a core outcome set (COS). Methods A systematic search was conducted to identify randomized controlled trials evaluating TCM interventions for acute pharyngitis. Data on study characteristics, outcome domains, specific outcomes, measurement instruments, and assessment time points were extracted. Outcomes were categorized using an established outcome taxonomy, and a narrative synthesis was performed to evaluate patterns of outcome reporting. Results A total of 182 studies were included. Six broad outcome domains comprising 817 individual outcomes were identified. Substantial heterogeneity was observed in outcome selection, definitions, and measurement approaches, with most outcomes reported in only a small proportion of studies. Symptom- and sign-based outcomes were universally reported, whereas domains such as quality of life, economic evaluation, and long-term prognosis were rarely addressed. Standardized patient-reported measures and validated instruments were infrequently used. In addition, outcome reporting was often limited to short-term clinical effects, with minimal integration of safety, patient-centered, or health system–level outcomes. Conclusion Substantial heterogeneity in outcome reporting across TCM trials for acute pharyngitis hinders cross-study comparison and evidence synthesis. This review provides an evidence base for developing a Core Outcome Set (COS) to standardize future outcome assessments and improve trial transparency.